THE CONFLICT OF STATE REGISTRATION AS A CONDITION FOR THE EMERGENCE OF A PUBLIC LEGAL DISPUTE - Olena S. Lunina (Alfred Nobel University Journal of Law)
The article is devoted to the study of the conflict of state registration as a condition for the emergence of a public legal dispute. The legal nature of state registration is determined, taking into account the determinant of conflict as a condition for the emergence of public legal disputes. It is noted that the development of justice in Ukraine should be aimed at strengthening the rule of law by ensuring access to justice, fair judicial procedures, independence, impartiality and professionalism of judges, as well as legal certainty, Uniformity of judicial practice and openness of judicial decisions, effectiveness of judicial protection. The article studies an opinion on determination of stages of development of legal conflict. The existing definitions of the concept of legal conflict have been analyzed, which is generally well-established in the doctrine of public law. A legal conflict is defined as a conflict between two or more actors based on the opposite or incompatibility of their interests, needs or values. The features of legal conflict are named: the connection of the conflict with legal relations, the presence of legal features of the subjects or the object of the conflict; the possibility of legal settlement; sectoral certainty of the conflict; the presence of legal consequences; the possibility of using coercive means in the conflict resolution process; conflict resolution through a special legal procedure. The doctrinal definitions of terms “registration”, “registration proceedings”, “state registration” were studied. The conclusion concerning the special character of the conflict of relations in the field of state registration is given, which is: that the improper exercise of authority by subjects in the field of state registration may violate not only the public rights of persons to properly carry out registration activities, but also the relevant rights, on the occurrence or implementation of which obstacles are created (ownership of real estate, the right to conduct business, etc.). The concepts of “foundation” and “conditions” of public-legal dispute are delimited. It is emphasized that the conflict of relations in the field of state registration as a condition for the emergence of public legal disputes is determined by the individual's interest in realizing, first of all, certain rights granted by law (rights to real estate, the right to carry out entrepreneurial activities, etc.), and not the rights to accept the subject of the authority of relevant decisions or actions.